Decoding The Obstacles of 10th Grade Student Learning in Atomic Structure at SMAN 1 Sungai Tarab - Nadila, Mutiara; Mawarnis, Elvy Rahmi (Universitas Pendidikan Mandalika, 2023)
This research uses qualitative research methods (descriptive). The subjects of this research were 10th grade students of Phase E.8 with a total of 28 students. Based on the research that has been done, it can be concluded that the results of the analysis of the types of learning difficulties and the factors that cause chemistry learning difficulties in 10th Grade students of atomic structure material at State Senior High School (SMAN) 1 Sungai Tarab are as follows. First, the types of chemistry learning difficulties consist of 3 types of difficulties including difficulty understanding terms with the highest percentage of 67.86% on the term atomic symbol, difficulty understanding concepts with the highest percentage of 67.86% on the concept of atomic structure according to Thomson and difficulty understanding numbers with the highest percentage of 64.28% on calculations or numbers looking for the number of values of atomic constituent particles (ions). Second, the factors causing chemistry learning difficulties consist of 2 factors, namely internal factors which include physical factors with a percentage of 32.14%, psychological factors with a percentage of 82.14% and emotional factors with a percentage of 71.43%, and external factors which include family factors with a percentage of 25%, school factors with a percentage of 35.71% and community factors with a percentage of 28.57%.